Understanding and Assessing Impact of Transmission and Distribution Projects on Electricity Access - Mittal, Rohit; Gupta, Amol; Gaba, Kwawu Mensan (World Bank, Washington, DC, 2019)
The North Eastern Region (NER) of India stretches across the eastern foothills of the Himalayan mountain range. Geographically, the region is connected to the other parts of the country through a small ‘chicken neck’ corridor in the state of West Bengal. With a total population of 45.6 million (2011 census), the sparsely populated NER covers 7.9 percent of India’s total geographical area. The vast majority of the region’s population (82 percent, 2011 census) lives in rural areas. The region possesses substantial estimated energy reserves, significant hydropower potential and natural gas reserves in the country. However, development in the NER has remained constrained due to several issues including deficit in physical infrastructure, poor connectivity, difficult and hilly terrain, etc. On the electricity access front, the region has a small and underdeveloped power system, with limited electricity access levels in rural areas and significant bottlenecks in the intra-state Transmission and Distribution (T&D) network.